2022
DOI: 10.5194/hess-26-3921-2022
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution satellite products improve hydrological modeling in northern Italy

Abstract: Abstract. Satellite-based Earth observations (EO) are an accurate and reliable data source for atmospheric and environmental science. Their increasing spatial and temporal resolutions, as well as the seamless availability over ungauged regions, make them appealing for hydrological modeling. This work shows recent advances in the use of high-resolution satellite-based EO data in hydrological modeling. In a set of six experiments, the distributed hydrological model Continuum is set up for the Po River basin (Ita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 82 publications
(85 reference statements)
1
31
0
Order By: Relevance
“…In terms of epistemic uncertainty, the S3M model relies on an enhanced temperature-index approach that was calibrated in Aosta valley and then extensively evaluated elsewhere in Italy (both in this paper and in other projects, such as Alfieri et al, 2022). While relying on the same parameters across the whole country could introduce some additional uncertainty at local scale, we highlight that results in this paper show a credible reconstruction of melt dynamics even in areas with only occasional assimilation (Figure 7), while Bouamri et al (2018) reported encouraging results when transferring model parameters of the same enhanced temperature-index approach to uncalibrated sites.…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…In terms of epistemic uncertainty, the S3M model relies on an enhanced temperature-index approach that was calibrated in Aosta valley and then extensively evaluated elsewhere in Italy (both in this paper and in other projects, such as Alfieri et al, 2022). While relying on the same parameters across the whole country could introduce some additional uncertainty at local scale, we highlight that results in this paper show a credible reconstruction of melt dynamics even in areas with only occasional assimilation (Figure 7), while Bouamri et al (2018) reported encouraging results when transferring model parameters of the same enhanced temperature-index approach to uncalibrated sites.…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…The model setup used here consisted of six modules (namely, the snow, vegetation, energy balance, soil, groundwater, and surface water modules) to simulate snow dynamics, vegetation interception, energy fluxes, evaporation from canopy layer, evapotranspiration, soil moisture and groundwater dynamics, and streamflow generation (Figure S1). Further, we simulated major lakes and dams in the region (Alfieri et al, 2022). We refer the reader to Silvestro et al (2013) for a description of the model, Silvestro et al (2015) for specifics on the snow module, and Silvestro et al (2021) for specifics on the surface flow routing scheme.…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…In this work, we run Continuum at a 0.009°(around 1 km) spatial resolution and 1 hour temporal resolution (Alfieri et al, 2022) over the hydrological years (h.y.) 2009 -2022, with the first h.y.…”
Section: Hydrological Modellingmentioning
confidence: 99%
See 2 more Smart Citations